Active Tumor Targeting: Active Targeting of Dendritic Polyglycerols for Diagnostic Cancer Imaging (Small 7/2020). Issue 7 (20th February 2020) - Pant, Kritee; Neuber, Christin; Zarschler, Kristof; Wodtke, Johanna; Meister, Sebastian; Haag, Rainer; Pietzsch, Jens; Stephan, Holger
Abstract : Nanosniffers to track down cancer: in article number 1905013, Kristof Zarschler, Holger Stephan, and co‐workers design and synthesize functionalized bimodal probes for diagnostic cancer imaging. These renally excretible, actively targeted nanomaterials specifically detect their molecular target and show superior tumor accumulation in vivo.